Systematized generation of animal welfare indicators for racing horses at racetracks in Santiago de Chile - Ugaz Ruiz, Cristian Marcel (2020)
This work focuses on the review of scientific literature to develop potential direct and indirect indicators of well-being of racehorses. In total, 149 indicators are described based on the principles and criteria of Welfare Quality®. Once the indicators were described, 32 experts dedicated to national equestrianism from various areas of knowledge and specialty (veterinarians, horse trainers of thoroughbreds, riders, foremen and keepers), evaluated the validity, reliability, feasibility in the field and acceptance of each indicator. Among the items with the most observations were those related to the provision and calculation of diet, health indicators and training practices. This research has explored some of the most relevant practical criteria in Chilean equestrian activity, to generate a valid and efficient tool, which will allow obtaining confidence from the main actors of this sporting activity.